The neural response to maternal stimuli: an ERP study. - Lili Wu; Ruolei Gu; Huajian Cai; Yu L L Luo; Jianxin Zhang (PLoS ONE, 2014)
Mothers are important to all humans. Research has established that maternal information affects individuals' cognition, emotion, and behavior. We measured event-related potentials (ERPs) to examine attentional and evaluative processing of maternal stimuli while participants completed a Go/No-go Association Task that paired mother or others words with good or bad evaluative words. Behavioral data showed that participants responded faster to mother words paired with good than the mother words paired with bad but showed no difference in response to these others across conditions, reflecting a positive evaluation of mother. ERPs showed larger P200 and N200 in response to mother than in response to others, suggesting that mother attracted more attention than others. In the subsequent time window, mother in the mother + bad condition elicited a later and larger late positive potential (LPP) than it did in the mother + good condition, but this was not true for others, also suggesting a positive evaluation of mother. These results suggest that people differentiate mother from others during initial attentional stage, and evaluative mother positively during later stage.